IDENTIFIKASI PENYEBAB TRANSGENDER PADA WARIA DI BANDA ACEH - Barmawi Barmawi; Miftahus Silmi (Psikoislamedia : Jurnal Psikologi, 2016)
This study aims to identify the factors causing the transgender transvestites in the city of Banda Aceh. Transgender is a term that is addressed to someone who can not identify specifically their sexual orientation, while transgender men is a normal man, who had a normal sex, but psychologically feel themselves as women. This study used a qualitative approach to the three respondents. And using the techniques of data collection through interviews, observation and field notes. The results showed that there are factors that cause the occurrence of transgender in Banda Aceh among other social factors of family, differences in parenting are applied in the family of each of the respondents gave a significant influence on the development.